Propuesta para aumentar la capacidad de producción de la planta de agua potable del centro sur del cantón Quevedo año 2014 - Morán Ortega, Elías Filemón (2015)
This research carried out with the aim of finding a solution to a problem that Quevedo city has that is the quality of water consumed by the population. So raised as the general objective "to make a proposal to increase the production capacity of the plant for drinking water, based on a technical study to the current modality of potabilization water from the south center of the canton Quevedo". The research was performed at the scene of the events; it used research techniques. In order to obtain quantitative information, a sample of 383 people polled was taken. Data relevant about to the project were determined, giving greater interest in investigation, in the technical study, of feasibility and economic financial study and the results were the basis for better decision making. The technical study resulted in the Canton Quevedo’s drinking water plant isn’t operative due to lack of maintenance of their facilities, taking as solution a complete reengineering (repowering) with an investment of US $ 872,481.68 for such works, being this awarded to the company INTAL. Investment capital has a depreciation rate of 12.5% per annum, equivalent to an annual depreciation of US $ 109,060.21 for 8 years that would be the lifetime of the equipment. With an annual income during the first year of 1,126,416, an NPV of $ 424,056.17, an IRR of 25% and a cost benefit of 1.19%.